Business Design Of Smoosh In South Jakarta - Malik Yahya Basalamah (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
The growth of the healthy beverage industry in Indonesia, particularly fruit-based smoothies, has increased along with rising public awareness of healthy lifestyles, especially among urban consumers. South Jakarta, with its large population of young professionals and health-conscious individuals, represents a promising market for affordable and practical healthy beverages. This study aims to develop a business design for SMOOSH, a mobile cart–based smoothie brand, by analyzing consumer needs, competitive conditions, and an appropriate Minimum Viable Product (MVP). This research employs a qualitative descriptive approach. Primary data were collected through semi-structured interviews with 11 consumers who had recently purchased SMOOSH products, while secondary data were obtained from market reports and competitor digital platforms. The analysis tools used in this study include the Value Proposition Canvas (VPC), Competitor Analysis Matrix, and the MVP framework. The findings indicate that SMOOSH’s customers prioritize freshness, natural taste, affordability, fast service, and friendly customer interaction. Competitor analysis shows that SMOOSH has strong advantages in price perception, product taste, and customer service compared to established brands such as Boost, Joomba, and Re.juve. However, brand image and packaging appeal still require improvement. The VPC analysis confirms a strong alignment between customer needs and SMOOSH’s value proposition, particularly in addressing pain points related to high prices, overly sweet flavors, and slow service. Based on these insights, the MVP is designed to focus on essential features, including fresh and natural smoothies, affordable pricing, a limited but focused menu, simple packaging, and efficient service. Overall, the results suggest that SMOOSH’s business design is feasible and well-aligned with market expectations, providing a strong foundation for sustainable business development in South Jakarta.